1967
DOI: 10.1136/bmj.2.5550.478
|View full text |Cite
|
Sign up to set email alerts
|

Observations of orthotopic liver transplantation in the pig.

Abstract: BRITISH certain of these changes occurred to a lesser degree in stress involution. The stress-involuted thymuses in our study showed the well-known change of cortical atrophy (Hammar, 1921), cystic Hassall's corpuscles, which have been observed in the involuted thymuses of guinea-pigs given cortisone or x-irradiation (Blau, 1965), and an increased percentage area of epithelial cell aggregates, these also being regarded by Lattes (1962) as associated with stress. The nature of these epithelial aggregates remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

1971
1971
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(24 citation statements)
references
References 3 publications
1
21
0
2
Order By: Relevance
“…The difficulty of engrafting adult thymocytes was first described in mice (21,100), but not with all strain combinations (103), Beyond its relevance to Monaco's research, the two-way paradigm allows reexamination of the literature on the inherent tolerogenicity of whole organs, much of which can be traced back to the 1969 report by Calne et al (104). It was already well known by then that canine liver allografts could self-induce tolerance during a 4-month postoperative course of azathioprine (105), and that this occurred even more frequently in untreated outbred pigs (106)(107)(108)(109)(110), many of which passed through spontaneously resolving rejection crises (109,111,112). First in pigs (104) and then in rodents (88,113,114), Calne, Zimmermann, and Kamada-and subsequently others (115, 116}-showed that the tolerization extended to other donor organs transplanted at the same time or later.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty of engrafting adult thymocytes was first described in mice (21,100), but not with all strain combinations (103), Beyond its relevance to Monaco's research, the two-way paradigm allows reexamination of the literature on the inherent tolerogenicity of whole organs, much of which can be traced back to the 1969 report by Calne et al (104). It was already well known by then that canine liver allografts could self-induce tolerance during a 4-month postoperative course of azathioprine (105), and that this occurred even more frequently in untreated outbred pigs (106)(107)(108)(109)(110), many of which passed through spontaneously resolving rejection crises (109,111,112). First in pigs (104) and then in rodents (88,113,114), Calne, Zimmermann, and Kamada-and subsequently others (115, 116}-showed that the tolerization extended to other donor organs transplanted at the same time or later.…”
Section: Discussionmentioning
confidence: 99%
“…It also is important to note that cessation of therapy was not followed by a graft versus host reaction." 12 The liver allograft was subsequently shown to selfinduce permanent tolerance without immunosuppression in at least 3 species: unpredictably in a significant minority of randomly paired outbred pigs, [13][14][15] invari-ably with a small number of strain combinations of inbred rats, 16,17 and in at least 50% of experiments in about 85% of all tested mouse strain pairings. 18 The self-induced tolerance is antigen-specific: ie, extends to other donor tissues and organs.…”
Section: Commentsmentioning
confidence: 99%
“…The immunological advantage of the liver relative to other organs includes a greater ease of inducing the acceptance of hepatic allografts or xenografts after a limited course of immunosuppression (4,25,132) or in swine (133)(134)(135) and some rat strain combinations (136,137) with no treatment at all. In addition, the transplanted liver graft is relatively resistant to the preformed antigraft antibodies that cause hyperacute rejection of the kidney and heart (138)(139)(140)(141).…”
Section: Hepatic Tolerogenicity and Its Implicationsmentioning
confidence: 99%